Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B.; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N.; Bainbridge, Matthew N.; Lawson, Kim S.; Pehlivan, Davut; et al. (Cell reports (Cambridge), 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity. [Display omitted] •WES of a neuropathy cohort identifies causal variants in ∼45% of patients•Three candidate disease genes associated with peripheral neuropathy are proposed•Evidence for genetic mutation burden is found in two independent cohorts•Variant combinatorial effects may contribute to clinical variability and expressivity Peripheral neuropathy is a clinically variable and genetically heterogeneous disease. In a cohort of patients, Gonzaga-Jauregui et al. have identified causative variants in ∼45% of the families studied, proposed candidate disease genes for an additional three families, and recognized a significant mutation burden in patients versus controls that likely contributes to phenotypic variability.